Integration of Ethnoscience in Science Learning: An Ethnoscience Study on the Palm Sugar Production Process - Rayis, Widuri Permata Anggarbini; Herayanti, Lovy; Prayogi, Saiful; Kurnia, Nova (Lensa: Jurnal Kependidikan Fisika, 2023)
This study explores the integration of ethnoscience into science education through the traditional process of palm sugar production in Mekarsari Village, Lombok, West Nusa Tenggara. Utilizing an exploratory research design, qualitative data were collected, and document analysis to examine the intersection between indigenous knowledge and scientific principles. The findings reveal that palm sugar production embodies fundamental scientific concepts. The study highlights how local farmers' expertise in tree selection, sap extraction, and sustainable processing methods aligns with modern scientific understanding. Furthermore, integrating palm sugar production into science curricula enhances students' competencies by fostering critical thinking, problem-solving, collaboration, and environmental awareness. Ethnoscience-based education also promotes character development, reinforcing values such as teamwork, responsibility, and respect for cultural heritage. Additionally, the study underscores the potential of this approach in equipping students with essential 21st-century skills, bridging traditional wisdom with contemporary scientific inquiry. By incorporating ethnoscience into formal education, this study demonstrates its effectiveness in creating a contextualized, interdisciplinary learning environment that respects both indigenous knowledge and modern scientific principles. The research concludes that integrating local wisdom into science education fosters sustainability, scientific literacy, and cultural appreciation, preparing students to navigate complex global challenges while preserving traditional knowledge systems.